DIVERSIFICATION IN PROPERTY UNIT TRUSTS - Kollenberg, Paul Leon (My University, 2011)
This research report investigates the Property Unit Trust (PUT) sector to assess if there are risk-sharing benefits to be obtained in building up a property portfolio. The report demonstrates that property trusts with diversified acquisition strategies achieve better risk sharing characteristics than those found in focused property funds. The ‘value at risk’ for each of the PUT’s was plotted over a 5-year period against the underlying asset value of the properties. This quantified the factor by which the ‘value at risk’ increased as the asset value increased. The values for each PUT were compared to the index for the sector, as well as separate indices for focused and diversified funds. The investigation demonstrated that property portfolios do provide an opportunity for risk sharing, and that diversified funds provide greater risk sharing possibilities. This finding is crucial to asset managers who assemble property funds in that it provides insight in combating portfolio volatility.
MBA thesis - WBS
Keywords: Property unit trusts; Unit trusts